Physicochemical and microbiological characterization of olive mill wastewater (OMW) from different regions of northern Morocco. Issue 23 (14th October 2020) - El Yamani, Mohamed; Sakar, El Hassan; Boussakouran, Abdelali; Ghabbour, Nabil; Rharrabti, Yahia
ABSTRACT: This work examined the influence of crop season, extraction system and production site on the composition of fresh olive mill wastewater collected from northern Morocco. ANOVA analysis showed that most of the traits were largely affected by the extraction system (≥60% of total variance). Comparison among extraction systems showed significant differences for all traits, except for chlorides. Three phase centrifugation system (C3) displayed the highest value of total phenols, while all the remaining traits were higher in two phase centrifugation system (C2). Concerning crop seasons, we noticed a general decrease in values of total solids, chemical oxygen demand, chlorides, C/N ratio and total aerobic mesophilic flora, from 2014 to 2016 season; in contrast, an increase in suspended solids, total kjeldahl nitrogen and proteins was detected. OMW with highest total phenols content and then more acidic were collected during 2015 season. Between production sites, Bni Frassen produced OMW with the highest values for salt and total phenols, but the lowest ones were obtained for microbiological traits. OMW from Taza were rich in total kjeldahl nitrogen and proteins. An increase in organic load indicators was observed in Bouchfaa. Principal component analysis (PCA) explained about 82% of total variability: 58%, 16% and 8% for principal component 1 (PC1), PC2 and PC3, respectively. Extraction system fitted the variability of PC1. PC2 was mainly explained by production sites, while PC3 separated crop seasons. Correlation studies showed significant relationships especially among the traits expressing organic load, while microbiological counts were largely associated to total phenols and pH. GRAPHICAL ABSTRACT: UF0001